Hard carbon negative electrode material and preparation method and application thereof

By using hard carbon anode materials with different particle sizes of specific volume ratios in sodium ion batteries and covering the amorphous carbon layer, the problem of insufficient performance of existing hard carbon anode materials in sodium ion batteries is solved, and the battery's high cycle performance, rate performance and energy density are achieved, and the production cost is reduced.

CN119812257APending Publication Date: 2025-04-11NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411951775.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing hard carbon anode materials have low compaction density, low tap density and low capacity in sodium ion batteries, which affect the cycling and rate performance of the battery.

Method used

A first hard carbon anode material and a second hard carbon anode material with a particle size of a specific volume ratio are used, and an amorphous carbon layer is coated on its surface, and a hard carbon anode material is prepared by one-step high-temperature calcination.

Benefits of technology

It improves the cycle performance, rate performance and energy density of the battery, reduces production costs, and enhances the purity and performance of hard carbon anode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812257A_ABST
    Figure CN119812257A_ABST
Patent Text Reader

Abstract

The invention provides a hard carbon negative electrode material as well as a preparation method and application thereof. The hard carbon negative electrode material comprises a hard carbon inner core and an amorphous carbon coating layer coating at least part of the surface of the hard carbon inner core, the hard carbon negative electrode material comprises a first hard carbon negative electrode material and a second hard carbon negative electrode material, the average particle size of the first hard carbon negative electrode material is 4-10 [mu] m, and the average particle size of the second hard carbon negative electrode material is 10.1-18 [mu] m; the ratio of the mass of the first hard carbon negative electrode material to the volume of the second hard carbon negative electrode material is (0.4-1.2): 1. According to the invention, the cycle performance, the rate capability and the energy density of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a hard carbon negative electrode material and a preparation method and application thereof, belonging to the technical field of secondary batteries. Background Art

[0002] Sodium-ion batteries are considered to be an effective supplement to lithium-ion batteries due to their abundant raw material reserves, low cost, and good low-temperature performance. They have great application potential in electric two-wheeled vehicles, low-speed electric vehicles, and energy storage systems. At present, the bottleneck of the industrialization of sodium-ion batteries lies mainly in the negative electrode material. The mainstream negative electrode material is hard carbon. The existing hard carbon negative electrode materials have the problems of high price, insufficient production capacity, and low industry maturity.

[0003] At present, hard carbon negative electrode materials are mainly prepared from biomass to reduce the cost of hard carbon negative electrode materials and increase the production capacity of hard carbon negative electrode materials. However, the hard carbon negative electrode materials prepared from biomass have the problems of low compaction density and low tap density, which affect the energy density of the battery; and the capacity of biomass hard carbon is relatively low, which makes the battery's cycle performance and rate performance poor. Summary of the invention

[0004] The present invention provides a hard carbon negative electrode material and a preparation method and application thereof. The special composition and morphology of the hard carbon negative electrode material enable the battery to improve its cycle performance, rate performance and energy density when applied to the battery.

[0005] The present invention provides a method for preparing the hard carbon negative electrode material. The method can prepare the hard carbon negative electrode material. The method is simple to operate and is suitable for wide promotion and application.

[0006] The present invention provides a battery, comprising the hard carbon negative electrode material, and the battery has excellent cycle performance, rate performance and energy density.

[0007] The present invention provides a hard carbon negative electrode material, which includes a hard carbon core and an amorphous carbon coating layer coated on at least a portion of the surface of the hard carbon core; the hard carbon negative electrode material includes a first hard carbon negative electrode material and a second hard carbon negative electrode material, the average particle size of the first hard carbon negative electrode material is 4-10 μm, and the average particle size of the second hard carbon negative electrode material is 10.1-18 μm; the volume ratio of the first hard carbon negative electrode material to the second hard carbon negative electrode material is (0.4-1.2):1.

[0008] In the hard carbon negative electrode material as described above, the carbon layer spacing of the amorphous carbon coating layer is 0.35-0.37 nm; and / or the thickness of the amorphous carbon coating layer is 1-20 nm.

[0009] The hard carbon negative electrode material as described above has a particle size volume distribution of 1-4.

[0010] The hard carbon negative electrode material as described above, wherein the carbon layer spacing of the hard carbon negative electrode material is

[0011] The hard carbon negative electrode material as described above, the powder impedance of the hard carbon negative electrode material is 8.0*10 -3 ~7.0*10 - 2 Ohm; and / or, the electronic conductivity of the hard carbon negative electrode material is 10-90S / cm.

[0012] The hard carbon negative electrode material as described above, wherein the compaction density of the hard carbon negative electrode material is 0.9-1.1 m2 / g; and / or the specific surface area of ​​the hard carbon negative electrode material is 0.5-7 m 2 / g; and / or, the content of metal impurities in the hard carbon negative electrode material is below 100ppm; and / or, the ash content of the hard carbon negative electrode material is ≤0.2%.

[0013] The present invention provides a method for preparing a hard carbon negative electrode material as described above, comprising: subjecting a carbon source to a hydrothermal reaction, and then pulverizing the carbon source to obtain a first spherical precursor and a second spherical precursor, wherein the D50 of the first spherical precursor is 4-10 μm, and the D50 of the second spherical precursor is 10.1-18 μm; mixing the first spherical precursor with the second spherical precursor to form a composite precursor, wherein the volume ratio of the first spherical precursor to the second spherical precursor is (0.4-1.2):1; mixing the composite precursor with a coating agent, and then calcining the composite precursor to obtain a hard carbon negative electrode material including an amorphous carbon coating layer; during the calcination process, the temperature is 1100-1600°C and the time is 1-10 hours.

[0014] In the preparation method as described above, in the hydrothermal reaction, the temperature is 200-360° C. and the time is 12-48 h; and / or the coating agent includes at least one of petroleum asphalt, coal tar, β resin, phenolic resin and epoxy resin.

[0015] The preparation method as described above, before the composite precursor is mixed with the coating agent, further comprises: performing a low-temperature oxygen-doping modification treatment on the composite precursor.

[0016] According to the preparation method described above, after the low-temperature oxygen doping modification treatment, the pH of the composite precursor is 3-4.5, and the oxygen doping amount of the composite precursor is 15-30wt%; and / or, during the low-temperature oxygen doping modification treatment, the temperature is 150-350°C and the time is 4-48h.

[0017] The present invention provides a battery, comprising the hard carbon negative electrode material as described above.

[0018] The present invention provides a hard carbon negative electrode material and a preparation method and application thereof, which have the following advantages:

[0019] The hard carbon negative electrode material of the present invention comprises a first hard carbon negative electrode material and a second hard carbon negative electrode material with different particle sizes in a specific volume ratio. When the hard carbon negative electrode material is applied to a battery, the first hard carbon negative electrode material with a smaller particle size can fill the gaps in the second hard carbon negative electrode material with a larger particle size to obtain a negative electrode sheet with a high compaction density, thereby improving the energy density of the battery; and the amorphous carbon coating layer of the hard carbon negative electrode material can reduce the probability of side reactions between the hard carbon negative electrode material and the electrolyte, effectively improving the cycle performance and rate performance of the battery;

[0020] The preparation method of the hard carbon negative electrode material of the present invention can prepare the above-mentioned hard carbon negative electrode material. The preparation method is simple to operate and is suitable for wide promotion and application. The preparation method adopts one-step high-temperature calcination, which can reduce the number of calcinations and reduce the production cost of the hard carbon negative electrode material.

[0021] The battery of the present invention comprises the hard carbon negative electrode material. Based on the hard carbon negative electrode material, the battery has excellent cycle performance, rate performance and energy density. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or related technologies, the following briefly introduces the drawings required for use in the embodiments of the present invention or related technologies. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0023] Figure 1 This is a SEM image of the hard carbon negative electrode material in Example 1 of the present invention;

[0024] Figure 2 This is a SEM image of the hard carbon negative electrode material in Comparative Example 4 of the present invention;

[0025] Figure 3 This is the XRD pattern of the hard carbon negative electrode material of Example 1 of the present invention;

[0026] Figure 4 is the XRD pattern of the amorphous carbon coating layer in Example 4 of the present invention;

[0027] Figure 5 This is the XRD diagram of the hard carbon negative electrode material in Comparative Example 4 of the present invention;

[0028] Figure 6The first cycle charge and discharge curve of the battery of the hard carbon negative electrode material in Example 1 of the present invention;

[0029] Figure 7 This is a first cycle charge and discharge curve diagram of the hard carbon negative electrode material in Comparative Example 4 of the present invention;

[0030] Figure 8 This is a high-resolution transmission electron microscope photograph of the amorphous coating layer in Example 4 of the present invention. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] A first aspect of the present invention provides a hard carbon negative electrode material, the hard carbon negative electrode material comprising a hard carbon core and an amorphous carbon coating layer coated on at least a portion of the surface of the hard carbon core;

[0033] The hard carbon negative electrode material comprises a first hard carbon negative electrode material and a second hard carbon negative electrode material, wherein the average particle size of the first hard carbon negative electrode material is 4-10 μm, and the average particle size of the second hard carbon negative electrode material is 10.1-18 μm;

[0034] The volume ratio of the first hard carbon negative electrode material to the second hard carbon negative electrode material is (0.4-1.2):1.

[0035] In the present invention, the amorphous carbon coating layer has an amorphous hard carbon structure, which is a non-graphitized amorphous carbon layer structure. It can be understood that the amorphous carbon coating layer of the present invention can be coated on the entire surface of the hard carbon core, or can be coated on a portion of the surface of the hard carbon core. The hard carbon negative electrode material of the present invention is a core-shell structure including a hard carbon core and an amorphous carbon coating layer from the inside to the outside.

[0036] For example, the average particle size of the first hard carbon negative electrode material with a smaller particle size can be 4, 6, 8, 10 μm or a range consisting of any two thereof, and the average particle size of the second hard carbon negative electrode material with a larger particle size can be 10.1, 12, 14, 15, 18 μm or a range consisting of any two thereof.

[0037] The hard carbon negative electrode material of the present invention comprises a first hard carbon negative electrode material with a smaller particle size and a second hard carbon negative electrode material with a larger particle size, and the volume ratio of the first hard carbon negative electrode material to the second hard carbon negative electrode material is (0.4-1.2):1, for example, 0.4:1, 1:1, 1.2:1 or a range consisting of any two of them.

[0038] It can be understood that when the density (true density) of the first hard carbon negative electrode material and the second hard carbon negative electrode material is close to or equal to each other, the volume ratio of the two materials can be approximated to or equal to the mass ratio of the two materials.

[0039] In some embodiments, a high-resolution transmission electron microscope can be used to test the hard carbon negative electrode material to obtain a TEM image of the hard carbon negative electrode material, and determine whether the hard carbon negative electrode material includes an amorphous coating layer based on the TEM image of the hard carbon negative electrode material; in addition, the hard carbon negative electrode material can be subjected to an SEM test to obtain an SEM image of the hard carbon negative electrode material, and determine the first hard carbon negative electrode material and the second hard carbon negative electrode material based on the SEM image of the hard carbon negative electrode material. In the SEM image, the hard carbon negative electrode material is divided into a first hard carbon negative electrode material with a particle size less than or equal to 10 μm and a second hard carbon negative electrode material with a particle size greater than 10 μm, and the average particle sizes of the first hard carbon negative electrode material and the second hard carbon negative electrode material are measured and calculated respectively. At the same time, the volume of the first hard carbon negative electrode material and the volume of the second hard carbon negative electrode material can also be obtained, and the volume ratio between the two can be calculated.

[0040] The hard carbon negative electrode material of the present invention comprises a first hard carbon negative electrode material and a second hard carbon negative electrode material with different particle sizes in a specific volume (mass) ratio. When the hard carbon negative electrode material is applied to a battery, the first hard carbon negative electrode material with a smaller particle size can fill the gaps in the second hard carbon negative electrode material with a larger particle size to obtain a negative electrode sheet with a high compaction density, thereby improving the energy density of the battery; and the amorphous carbon coating layer of the hard carbon negative electrode material can reduce the probability of side reactions between the hard carbon negative electrode material and the electrolyte, effectively improving the cycle performance and rate performance of the battery.

[0041] In some embodiments of the present invention, the (002) carbon interlayer spacing of the amorphous carbon coating layer is 0.35-0.37 nm.

[0042] In some embodiments, the (002) carbon interlayer spacing of the amorphous carbon coating layer can be obtained according to the XRD spectrum of the hard carbon negative electrode material. When the (002) carbon interlayer spacing of the amorphous carbon coating layer meets the above range, the carbon interlayer spacing of the amorphous carbon coating layer is large, which can increase the sodium storage active sites and the reversible capacity of the hard carbon negative electrode material.

[0043] In some embodiments of the present invention, when the thickness of the amorphous carbon coating layer is 1-20 nm, the amorphous carbon coating layer can better protect the hard carbon core while ensuring the capacity of the hard carbon negative electrode material, thereby avoiding side reactions between the hard carbon core and the electrolyte and improving the cycle performance and rate performance of the battery. In some embodiments, the thickness of the amorphous coating layer can be obtained by TEM.

[0044] In some embodiments of the present invention, the particle size volume distribution of the hard carbon negative electrode material is 1-4.

[0045] Particle size volume distribution SPAN = (D90-D10) / D50. When the particle size volume distribution of the hard carbon negative electrode material meets the above range, the larger second hard carbon negative electrode material can better match the smaller first hard carbon negative electrode material, thereby improving the energy density of the battery.

[0046] The inventors also found in their research that when the (002) carbon layer spacing of the hard carbon negative electrode material is When the hard carbon negative electrode material has more sodium storage active sites, the reversible capacity of the hard carbon negative electrode material can be further improved. In some embodiments, the (002) carbon layer spacing of the hard carbon negative electrode material can be obtained according to the XRD spectrum of the hard carbon negative electrode material.

[0047] In some embodiments of the present invention, the powder impedance of the hard carbon negative electrode material is 8.0*10 -3 ~7.0*10 - 2 Ohm.

[0048] In the present invention, the powder impedance of the hard carbon negative electrode material refers to the powder impedance of the hard carbon negative electrode material under 16-20 MPa. When the powder impedance of the hard carbon negative electrode material meets the above range, the hard carbon negative electrode material can further improve the rate performance of the battery.

[0049] Furthermore, when the electronic conductivity of the hard carbon negative electrode material is 10-90 S / cm, the obtained battery has better rate performance.

[0050] In some embodiments of the present invention, the compaction density of the hard carbon negative electrode material is 0.9-1.1 m 2 / g.

[0051] In the present invention, the compaction density of the hard carbon negative electrode material refers to the compaction density of the hard carbon negative electrode material under a pressure of 1 T. When the compaction density of the hard carbon negative electrode material satisfies the above range, the energy density of the battery can be further improved.

[0052] The inventors also found that when the specific surface area of ​​the hard carbon negative electrode material is 0.5-7m 2 / g, the hard carbon negative electrode material can undergo more complete electrochemical reactions when used in batteries, thereby improving the battery's rate performance, energy density, and cycle performance.

[0053] Furthermore, in the hard carbon negative electrode material, the content of metal impurities is below 100 ppm; and / or, the ash content of the hard carbon negative electrode material is ≤0.2%, indicating that the purity of the hard carbon negative electrode material of the present invention is high, which can further improve the rate performance, energy density and cycle performance of the battery. In some embodiments, the total metal impurity content of the hard carbon negative electrode material can be tested using an inductively coupled plasma optical emission spectrometer (ICP-OES).

[0054] A second aspect of the present invention provides a method for preparing the hard carbon negative electrode material, comprising:

[0055] After the carbon source is subjected to a hydrothermal reaction, it is crushed to obtain a first spherical precursor and a second spherical precursor, wherein the D50 of the first spherical precursor is 4-10 μm, and the D50 of the second spherical precursor is 10.1-18 μm;

[0056] The first spherical precursor and the second spherical precursor are mixed to form a composite precursor, wherein the volume ratio of the first spherical precursor to the second spherical precursor is (0.4-1.2):1;

[0057] After the composite precursor and the coating agent are mixed, a calcination treatment is performed to obtain a hard carbon negative electrode material including an amorphous coating layer; during the calcination treatment, the temperature is 1100-1600° C. and the time is 1-10 hours.

[0058] Specifically, a carbon source is subjected to a hydrothermal reaction to form a spherical precursor, and then the spherical precursor is crushed to obtain spherical precursors of different particle sizes, and a first spherical precursor with a D50 of 4-10 μm and a second spherical precursor with a D50 of 10.1-18 μm are mixed in a volume ratio of (0.4-1.2):1 to form a composite precursor;

[0059] After the composite precursor and the coating agent are mixed, calcination treatment is carried out at 1100-1600°C for 1-10h. During the calcination treatment, the coating agent will form an amorphous hard carbon coating layer coating the surface of the hard carbon core; and the first spherical precursor will fill part of the voids formed by the second spherical precursor to obtain a hard carbon negative electrode material with excellent spherical morphology.

[0060] The method for preparing the hard carbon negative electrode material of the present invention can obtain the hard carbon negative electrode material mentioned above, and the preparation method adopts one-step high-temperature calcination, which can reduce the number of calcinations and reduce the production cost of the hard carbon negative electrode material.

[0061] The present invention does not particularly limit the carbon source, and the carbon source can be a material commonly used in the art that can form carbon after calcination. In some embodiments, the carbon source can be a biomass carbon source, and further, the carbon source can be at least one of glucose, starch, and sucrose. Since the impurity content in glucose, starch, and sucrose is relatively low, using glucose, starch, and sucrose as carbon sources can not only obtain hard carbon negative electrode materials with low impurity content and low ash content, but also can eliminate the need for additional, complex purification processes, and can avoid impurity removal steps such as acid washing, alkali washing, and water washing, which is beneficial to reducing environmental pollution and reducing the production cost of hard carbon negative electrode materials.

[0062] In some embodiments, the pulverization process may be an air pulverization process, and after the pulverization process, a sieving process is performed to obtain a spherical precursor with a particle size of 4-18 μm.

[0063] The present invention does not specifically limit the coating agent, and the coating agent can be a material commonly used in the art that forms a carbon coating layer after calcination. Exemplarily, the coating agent can be at least one of petroleum asphalt, coal asphalt, β resin, phenolic resin and epoxy resin. And the amount of the coating agent added can be 0.5-20% of the total mass of the composite precursor and the coating agent, thereby forming an amorphous carbon coating layer with a coating thickness of 1-20nm.

[0064] In some embodiments of the present invention, when the temperature is 200-360°C and the time is 12-48h in the hydrothermal reaction, the carbon source can be more fully converted into a spherical precursor with less impurity content, thereby promoting subsequent reactions and obtaining a hard carbon negative electrode material with excellent comprehensive performance.

[0065] In some embodiments of the present invention, before the composite precursor is mixed with the coating agent, the process further includes: subjecting the composite precursor to a low-temperature oxygen-doping modification treatment.

[0066] Specifically, it also includes: performing low-temperature oxygen-doping modification treatment on the composite precursor to obtain an oxygen-doped composite precursor, and then mixing the oxygen-doped composite precursor with a coating agent, and then performing calcination treatment to obtain a hard carbon negative electrode material including an amorphous coating layer.

[0067] In some embodiments, the low-temperature oxygen-doping modification treatment may be performed in an oxygen-containing atmosphere, and the oxygen-containing atmosphere may be at least one of air, oxygen, and oxygen-containing nitrogen.

[0068] Before the composite precursor is mixed with the coating agent, the present invention also performs low-temperature oxygen doping modification treatment on the composite precursor, which can hinder the graphitization of the composite precursor, increase the carbon layer spacing of the hard carbon negative electrode material (002), and further increase the sodium storage site and reversible capacity of the hard carbon negative electrode material.

[0069] Furthermore, after low-temperature oxygen doping modification treatment, the pH of the composite precursor is 3-4.5, and the oxygen doping amount of the composite precursor is 15-30wt%; and / or, during the low-temperature oxygen doping modification treatment, when the temperature is 150-350°C and the time is 4-48h, the graphitization of the composite precursor can be further hindered, the carbon layer spacing of the hard carbon negative electrode material (002) can be increased, and the sodium storage sites and reversible capacity of the hard carbon negative electrode material can be increased.

[0070] In some embodiments, the hard carbon negative electrode material may be crushed and sieved to obtain a hard carbon negative electrode material of a target size. Further, the mesh size of the sieve may be 300-500 meshes.

[0071] A third aspect of the present invention provides a battery, comprising the hard carbon negative electrode material of the first aspect.

[0072] In the present invention, the hard carbon negative electrode material can be prepared into a negative electrode sheet using a method commonly used in the art, and then the negative electrode sheet is assembled with a positive electrode sheet commonly used in the art to obtain a battery.

[0073] The battery of the present invention, because it includes the hard carbon negative electrode material of the first aspect, has excellent rate performance, energy density and cycle performance.

[0074] The technical solution of the present invention will be further explained below in conjunction with specific embodiments.

[0075] Example 1

[0076] Preparation of hard carbon negative electrode materials

[0077] 1) After the biomass raw material is subjected to a hydrothermal reaction, it is subjected to a gas crushing treatment to obtain a first spherical precursor and a second spherical precursor, and the first spherical precursor and the second spherical precursor are mixed to form a composite precursor;

[0078] The biomass raw material is glucose; in the hydrothermal reaction, the temperature is 200°C and the time is 12h; the D50 of the first spherical precursor is 6μm, and the D50 of the second spherical precursor is 15μm; in the composite precursor, the volume ratio (R) of the first spherical precursor to the second spherical precursor is 0.4:1;

[0079] 2) performing low-temperature oxygen-doping modification treatment on the composite precursor in an oxygen-containing atmosphere to obtain an oxygen-doped composite precursor;

[0080] The oxygen-containing atmosphere is air; the pH of the oxygen-doped composite precursor is 3.6, and the oxygen doping amount is 24% (obtained by EDS test); in the low-temperature oxygen-doping modification treatment, the temperature is 300° C. and the time is 8 hours.

[0081] 3) mixing the composite precursor after low-temperature oxygen-doped modification treatment and the coating agent to form a mixture, and calcining the mixture under nitrogen protection to obtain a hard carbon negative electrode material including an amorphous carbon coating layer;

[0082] The coating agent is coal tar pitch; the mass percentage of the coating agent in the mixture is 5%; during the calcination treatment, the temperature is raised from room temperature to 1300°C at a heating rate of 3°C / min, and the temperature is kept for 5 hours, and the thickness of the amorphous carbon coating layer is 20nm;

[0083] 4) The hard carbon negative electrode material balls were crushed and passed through a 325-mesh sieve to obtain a 325-mesh hard carbon negative electrode material.

[0084] Example 2

[0085] The preparation method of the hard carbon negative electrode material of this embodiment is basically the same as that of Example 1, except that: in step 1), the volume ratio of the first spherical precursor to the volume of the second spherical precursor is 1:1; other conditions remain unchanged.

[0086] Example 3

[0087] The preparation method of the hard carbon negative electrode material of this embodiment is basically the same as that of Embodiment 1, except that: in step 2), the temperature in the low-temperature oxygen-doping modification treatment is 150° C.; other conditions remain unchanged.

[0088] Example 4

[0089] The preparation method of the hard carbon negative electrode material of this embodiment is basically the same as that of embodiment 1, except that in step 2), the temperature of the low-temperature oxygen-doping modification treatment is 250° C.;

[0090] In step 3), in the mixture, the coating agent is β resin; other conditions remain unchanged.

[0091] Example 5

[0092] The preparation method of the hard carbon negative electrode material of this embodiment is basically the same as that of embodiment 1, except that: in step 3), in the mixture, the coating agent is β resin, and the mass percentage of the coating agent is 3%; other conditions remain unchanged.

[0093] Example 6

[0094] The preparation method of the hard carbon negative electrode material of this embodiment is basically the same as that of Example 1, except that: in step 3), the coating agent in the mixture is β resin, and the mass percentage of the coating agent is 3%; during the calcination treatment, the temperature is 1500°C; other conditions remain unchanged.

[0095] Example 7

[0096] The preparation method of the hard carbon negative electrode material in this embodiment is basically the same as that in embodiment 1, except that:

[0097] Excluding step 2);

[0098] In step 3), the composite precursor and the coating agent are mixed to form a mixture; other conditions remain unchanged.

[0099] Example 8

[0100] The preparation method of the hard carbon negative electrode material in this embodiment is basically the same as that in embodiment 1, except that:

[0101] The D50 of the first spherical precursor is 4 μm, and the D50 of the second spherical precursor is 10.1 μm; in the composite precursor, the volume ratio (R) of the first spherical precursor to the second spherical precursor is 1.2:1; other conditions remain unchanged.

[0102] Example 9

[0103] The preparation method of the hard carbon negative electrode material in this embodiment is basically the same as that in embodiment 1, except that:

[0104] The D50 of the first spherical precursor is 10 μm, and the D50 of the second spherical precursor is 18 μm; in the composite precursor, the volume ratio (R) of the first spherical precursor to the second spherical precursor is 0.8:1; other conditions remain unchanged.

[0105] Example 10

[0106] The preparation method of the hard carbon negative electrode material in this embodiment is basically the same as that in embodiment 1, except that:

[0107] The D50 of the first spherical precursor is 6 μm, and the D50 of the second spherical precursor is 12 μm; in the composite precursor, the volume ratio (R) of the first spherical precursor to the second spherical precursor is 1:1; other conditions remain unchanged.

[0108] Embodiment 11

[0109] The preparation method of the hard carbon negative electrode material in this embodiment is basically the same as that in embodiment 1, except that:

[0110] Step 2) is not included, that is, low-temperature oxygen-doping modification treatment is not included; other conditions remain unchanged.

[0111] Comparative Example 1

[0112] The preparation method of the hard carbon negative electrode material in this comparative example is basically the same as that in Example 1, except that:

[0113] In step 1), the biomass raw material is subjected to a hydrothermal reaction and then subjected to a gas crushing treatment to obtain a spherical precursor with a D50 of 15 μm;

[0114] Excluding step 2);

[0115] In step 3), the spherical precursor is calcined under the protection of nitrogen to obtain a hard carbon negative electrode material.

[0116] Comparative Example 2

[0117] The preparation method of the hard carbon negative electrode material in this comparative example is basically the same as that in Example 1, except that:

[0118] In step 1), the biomass raw material is subjected to a hydrothermal reaction and then subjected to a gas crushing treatment to obtain a spherical precursor with a D50 of 15 μm;

[0119] In step 2), the spherical precursor is subjected to low-temperature oxygen-doping modification treatment in an oxygen-containing atmosphere to obtain a spherical precursor after low-temperature oxygen-doping modification treatment;

[0120] In step 3), the spherical precursor after low-temperature oxygen-doping modification is calcined under nitrogen protection to obtain a hard carbon negative electrode material.

[0121] Comparative Example 3

[0122] The preparation method of the hard carbon negative electrode material in this comparative example is basically the same as that in Example 1, except that:

[0123] In step 1), the biomass raw material is subjected to a hydrothermal reaction and then subjected to a gas crushing treatment to obtain a spherical precursor with a D50 of 15 μm.

[0124] Comparative Example 4

[0125] The preparation method of the hard carbon negative electrode material in this comparative example is basically the same as that in Example 1, except that:

[0126] In step 3), no coating agent is added.

[0127] Test example

[0128] The hard carbon negative electrode materials in the embodiment and the comparative example are used to prepare batteries, specifically comprising:

[0129] 1) Preparation of negative electrode

[0130] The hard carbon negative electrode material, conductive carbon black and sodium carboxymethyl cellulose are placed in a slurry mixer according to a mass ratio of 80:10:10, and then nitrogen methyl pyrrolidone solvent is added and mixed evenly to obtain a negative electrode slurry, and the negative electrode slurry is evenly coated on the two surfaces of the carbon-coated aluminum foil respectively, and placed in a vacuum drying oven at 100° C. for 12 hours to obtain a negative electrode sheet;

[0131] 2) Preparation of batteries

[0132] Metallic sodium was used as the counter electrode to assemble with the negative electrode sheet of step 1), glass fiber was used as the separator, and 1.5 mol / L sodium hexafluorophosphate (NaPF6) dimethyl carbonate (DMC), ethylene carbonate (EC) and ethyl methyl carbonate (EMC) (volume ratio 2:1:2) were used as the electrolyte to assemble a CR2032 battery.

[0133] Performance Testing

[0134] 1) SEM test

[0135] The SEM images of the hard carbon negative electrode materials in Example 1 and Comparative Example 4 were obtained respectively. Figure 1 This is a SEM image of the hard carbon negative electrode material in Example 1 of the present invention; Figure 2 This is a SEM image of the hard carbon negative electrode material in Comparative Example 4 of the present invention. Figure 1 and Figure 2 It can be seen that the hard carbon negative electrode material in Example 1 has a coating layer. The average particle size of the hard carbon negative electrode material was measured by Nano Measurer 1.2 on the SEM image, where Figure 1 The average particle size of the hard carbon in Example 1 is 10.51 μm. Figure 2 The average particle size of the hard carbon in Comparative Example 4 was 10.70 μm.

[0136] 2) XRD test

[0137] The β resin was calcined in a nitrogen atmosphere using the calcination parameters in Example 4 to obtain an amorphous carbon coating layer with a thickness of 20 nm.

[0138] The XRD graph of the hard carbon negative electrode material in Example 1, the XRD graph of the amorphous carbon coating layer in Example 4, and the XRD graph of the hard carbon negative electrode material in Comparative Example 4 were obtained respectively.

[0139] Figure 3 This is the XRD pattern of the hard carbon negative electrode material of Example 1 of the present invention; Figure 4 is the XRD pattern of the amorphous carbon coating layer in Example 4 of the present invention; Figure 5 This is the XRD diagram of the hard carbon negative electrode material in Comparative Example 4 of the present invention. Figure 3 It can be seen that the hard carbon negative electrode material in Example 1 of the present invention has two large bulge peaks (typical amorphous carbon characteristic peaks), and its (002) crystal plane spacing d(002) is from Figure 4 It can be seen that an amorphous carbon coating layer is formed in Example 4, and the (002) crystal plane spacing of the amorphous carbon coating layer is 0.35 nm. Figure 3 and Figure 4 It can be seen that in the preparation of the hard carbon negative electrode material in Example 1, the coating agent forms a non-graphitized amorphous carbon layer structure after high-temperature carbonization, just like the amorphous hard carbon structure. Therefore, the XRD of the hard carbon negative electrode material in Example 1 has no other characteristic peaks except two large bulging peaks.

[0140] from Figure 5 It can be seen that the X-ray diffraction pattern of the hard carbon negative electrode material of Comparative Example 4 of the present invention has two large bulge peaks, which also shows typical amorphous carbon characteristics, and its (002) crystal plane spacing d(002) is

[0141] 3) Powder impedance

[0142] The powder impedance was measured using the four-probe method according to the national standard GB / T 30835-2014.

[0143] 4) Electronic conductivity

[0144] The electronic conductivity was calculated using the four-probe method according to the national standard GB / T 30835-2014.

[0145] 5) BET

[0146] The specific surface area BET was obtained by using BEST 3H-2000BET-A according to the national standard GB / T 19587-2017.

[0147] 6) Compacted density

[0148] The powder compaction density is based on the national standard GB / T 24533-2019, using a pressure mold and tested at 1.0T pressure for 30s.

[0149] 7) Average particle size of the first hard carbon negative electrode material A1, average particle size of the second hard carbon negative electrode material A2, SPAN

[0150] A SEM test is performed on the hard carbon negative electrode material to obtain an SEM image of the hard carbon negative electrode material, and a first hard carbon negative electrode material and a second hard carbon negative electrode material are determined according to the SEM image of the hard carbon negative electrode material. In the SEM image, 10 μm is used as a dividing line to divide the hard carbon negative electrode material into a first hard carbon negative electrode material with a particle size less than or equal to 10 μm and a second hard carbon negative electrode material with a particle size greater than 10 μm. The average particle sizes of the first hard carbon negative electrode material and the second hard carbon negative electrode material are measured and calculated respectively, and the volume of the first hard carbon negative electrode material and the volume of the second hard carbon negative electrode material can also be obtained, and the volume ratio R between the two can be calculated.

[0151] The SPAN value is calculated from the particle size distribution data of the overall hard carbon negative electrode material tested using a Malvern 3000 laser particle size analyzer, SPAN = (D90-D10) / D50.

[0152] 8) Thickness of amorphous carbon coating

[0153] The thickness of the amorphous carbon coating layer was measured by high-resolution transmission electron microscopy. Figure 8 The figure shows a high-resolution transmission electron microscope photograph of the amorphous coating layer in Example 4. The coating layer thickness is measured to be about 8 nm.

[0154] 9) Metal impurity content and ash content

[0155] The content of metal impurities is tested by inductively coupled plasma optical emission spectrometry (ICP-OES); the ash content is tested according to the national standard GB / T 17664-1999.

[0156] 10) Charge and discharge performance

[0157] The button cell was subjected to constant current charge and discharge tests on a Xinwei multi-channel test system at 25°C, with a voltage of 0-2.0V, a rate of 0.1C, and 1C = 300mA / g.

[0158] Figure 6 is a first cycle charge and discharge curve diagram of a battery including the hard carbon negative electrode material in Example 1 of the present invention; Figure 7 The first cycle charge and discharge curve of the hard carbon negative electrode material in Comparative Example 4 of the present invention is shown in FIG. Figure 6 and Figure 7 It can be seen that the hard carbon negative electrode material in Example 1 has a relatively high reversible specific capacity and first coulombic efficiency, wherein the reversible specific capacity is 330 mAh / g and the first coulombic efficiency is 93%.

[0159] Test results

[0160] Table 1

[0161]

[0162]

[0163] Table 2

[0164]

[0165]

[0166] Table 3

[0167]

[0168]

[0169] It can be seen from Table 1, Table 2 and Table 3 that the hard carbon negative electrode material in the embodiment of the present invention has the characteristics of high compaction density, low impurities, high reversible specific capacity, good battery cycle performance and rate performance.

[0170] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A hard carbon negative electrode material, characterized in that: The hard carbon negative electrode material comprises a hard carbon core and an amorphous carbon coating layer coated on at least a portion of the surface of the hard carbon core; The hard carbon negative electrode material comprises a first hard carbon negative electrode material and a second hard carbon negative electrode material, wherein the average particle size of the first hard carbon negative electrode material is 4-10 μm, and the average particle size of the second hard carbon negative electrode material is 10.1-18 μm; The volume ratio of the first hard carbon negative electrode material to the second hard carbon negative electrode material is (0.4-1.2):

1.

2. The hard carbon negative electrode material according to claim 1, characterized in that: The carbon interlayer spacing of the amorphous carbon coating layer is 0.35-0.37 nm; and / or, The thickness of the amorphous carbon coating layer is 1-20 nm.

3. The hard carbon negative electrode material according to claim 1 or 2, characterized in that: The particle size volume distribution of the hard carbon negative electrode material is 1-4.

4. The hard carbon negative electrode material according to any one of claims 1 to 3, characterized in that: The carbon interlayer spacing of the hard carbon negative electrode material is 5. The hard carbon negative electrode material according to any one of claims 1 to 4, characterized in that: The powder impedance of the hard carbon negative electrode material is 8.0*10 -3 ~7.0*10 -2 Ohm; and / or, The electronic conductivity of the hard carbon negative electrode material is 10-90S / cm.

6. The hard carbon negative electrode material according to any one of claims 1 to 5, characterized in that: The compaction density of the hard carbon negative electrode material is 0.9-1.1 m 2 / g; and / or, The specific surface area of ​​the hard carbon negative electrode material is 0.5-7m 2 / g; and / or, The content of metal impurities in the hard carbon negative electrode material is below 100 ppm; and / or the ash content of the hard carbon negative electrode material is ≤0.2%.

7. A method for preparing the hard carbon negative electrode material according to any one of claims 1 to 6, characterized in that: include: After the carbon source undergoes a hydrothermal reaction, it is crushed to obtain a first spherical precursor and a second spherical precursor, wherein the D50 of the first spherical precursor is 4-10 μm, and the D50 of the second spherical precursor is 10.1-18 μm; The first spherical precursor and the second spherical precursor are mixed to form a composite precursor, wherein the volume ratio of the first spherical precursor to the second spherical precursor is (0.4-1.2):1; After the composite precursor is mixed with the coating agent, a calcination treatment is performed to obtain a hard carbon negative electrode material including an amorphous carbon coating layer; during the calcination treatment, the temperature is 1100-1600° C. and the time is 1-10 hours.

8. The preparation method according to claim 7, characterized in that: In the hydrothermal reaction, the temperature is 200-360°C and the time is 12-48h; And / or, the coating agent includes at least one of petroleum asphalt, coal tar, beta resin, phenolic resin and epoxy resin.

9. The preparation method according to claim 7 or 8, characterized in that: Before the composite precursor is mixed with the coating agent, the method further includes: performing low-temperature oxygen-doping modification treatment on the composite precursor.

10. The preparation method according to claim 9, characterized in that: After the low-temperature oxygen-doping modification treatment, the pH of the composite precursor is 3-4.5, and the oxygen-doping amount of the composite precursor is 15-30 wt %; and / or, In the low-temperature oxygen-doping modification treatment, the temperature is 150-350° C. and the time is 4-48 hours.

11. A battery, characterized in that: The hard carbon negative electrode material comprises the hard carbon negative electrode material according to any one of claims 1 to 6.

Citation Information

Cited By

  • Hard carbon negative electrode material, and preparation method therefor and use thereof

    WO2026137788A1